Perceptual Correlates of Acoustic Measures of Vocal Variability - (:unkn) unknown (My University, 2013)
This study investigated relationships between acoustic measures of vocal variability (pitch sigma, SFF range) and perceptual ratings of vocal variability during a reading task. Fifteen male (19-30 years of age) and nineteen female speakers (20-30 years of age) who were recorded reading the Grandfather Passage provided the stimuli for the listening task. From these samples, 30 were selected as representing a continuum of degrees of vocal variability. Male (N = 15) and female (N = 15) samples were presented to listeners separately. Thirty graduate students in Communication Sciences and Disorders who had a course background in voice supplied the perceptual judgments of these samples. The listeners provided perceptual judgments of vocal variability on a 7-point Likert scale (1 defined as “complete monotone” and 7 defined as “extreme variability”). Results indicated a strong positive correlation between acoustic measures of vocal variability and listener judgments of pitch variability, significant at the p This study also investigated whether acoustic measures of vocal variability (pitch sigma, SFF range) in males differ significantly from these acoustic measures of vocal variability in females. Results showed no significant differences between male and female voices for either acoustic measure. Additional research is needed to determine whether there are differences between male and female voices in terms of perceptual measures of vocal variability. This study also reported speaking fundamental frequency (SFF) characteristics of young adults during reading. Chosen measures included mean SFF, pitch sigma, and SFF range. Results showed that males averaged an SFF of 122.73 Hz, a pitch sigma of 2.18 STs, and an SFF range of 11.33 STs. Females averaged an SFF of 215.92 Hz, a pitch sigma of 2.27 STs, and an SFF range of 12.05 STs. Comparisons with earlier literature revealed differences, possibly relating to adjustment of analysis range.
Keywords: Acoustic Measures; Gender Differences; Perceptual Measures; Pitch Sigma; Speaking Fundamental Frequency Range; Vocal Variability